2022
DOI: 10.3389/fenrg.2022.1017293
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of dust pollutants and the impact of suspended particulate matter on the performance of photovoltaic systems

Abstract: The purpose of this study is to investigate the potential of airborne particulate matter (PM10 and PM2.5) and its impact on the performance of the photovoltaic (PV) system installed in the Sargodha region, being affected by the crushing activities in the hills. More than 100 stone crushers are operating in this region. Four stations within this region are selected for taking samples during the summer and winter seasons. Glass–fiber papers are used as a collection medium for particulate matter (PM) in a high-vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 67 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…[9,10] In this context, the appropriate utilization of renewable energy resources in rural or remote areas may be a feasible, practical, and cost-effective option for extending the existing energy distribution system. [11][12][13] Renewable energy (RE) resources such as solar (PV), geothermal wind, biomass, and hydro can serve as possible sources of alternative energy due to their inexhaustibility, accessibility onsite, cost-free nature, and environmental friendliness, especially for local energy generation in isolated rural locations. After the rising oil crisis, there has been increasing interest in their utilization.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[9,10] In this context, the appropriate utilization of renewable energy resources in rural or remote areas may be a feasible, practical, and cost-effective option for extending the existing energy distribution system. [11][12][13] Renewable energy (RE) resources such as solar (PV), geothermal wind, biomass, and hydro can serve as possible sources of alternative energy due to their inexhaustibility, accessibility onsite, cost-free nature, and environmental friendliness, especially for local energy generation in isolated rural locations. After the rising oil crisis, there has been increasing interest in their utilization.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9,10 ] In this context, the appropriate utilization of renewable energy resources in rural or remote areas may be a feasible, practical, and cost‐effective option for extending the existing energy distribution system. [ 11–13 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The performance of photovoltaic array is dependent on ambient temperature, intensity of solar irradiation, and the surface temperatures on the both sides (bottom and top) of modules [ 38 ]. These factors fluctuate throughout the year for a particular region depending on the season [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…[26] Tamoor et al studied the influence of particulate matter (PM10 and PM2.5) in the air on the power generation performance of photovoltaic systems in the Sargodha area, which found that the deposition of aerosol particles causes the output power of PV modules to decrease in all months compared with clean photovoltaic modules. [27] Song et al showed that air pollutants and pollutants attached to the surface of PV modules could significantly reduce the power generation efficiency of PV modules. [28] Some researchers discussed the influencing factors of n, and the influence law or level of different influencing factors on n was analyzed.…”
Section: Introductionmentioning
confidence: 99%